Energy efficient routing and task scheduling for autonomous transfer vehicles in intra logistics - İnci Sarıçiçek; Sinem Bozkurt Keser; Azmi Cibi; Tahir Özdemir; Ahmet Yazıcı (Kuwait Journal of Science)
An energy efficient routing and scheduling system is proposed to minimize the total energy that the vehicles spend. Not only travelled distance but also the load of the vehicle is considered between two points. The routes of vehicles are obtained by using the proposed Hybrid Simulated Annealing Algorithm. An algorithm for the initial solution is also proposed to determine the minimum number of vehicles for pickup and delivery requests. The performance of the algorithm is compared with the best solutions of the test problems in the literature. Besides, the proposed energy efficient routing and task scheduling model is compared with the classical distance model for routing and scheduling with backhauls. An analysis of trade-offs between energy and distance is proposed for intra logistics. Experimental results show that while energy saving is 18.11%, the total distance increases as 12.08% in total for test problems.